Efficiency of rice straw lignocelluloses degradability by Aspergillus terreus ATCC 74135 in solid state fermentation - Jahromi, Mohammad Faseleh; Liang, Juan Boo; Mohamad, Rosfarizan; Goh, Yong Meng; Shokryazdan, Parisa; Ho, Yin Wan (Academic Journals, 2011)
The ability of Aspergillus terreus for the production of cellulolytic enzymes and reduction of lignocellulose contents of rice straw in solid state fermentation was investigated in this study. Results suggested that, 8 days fermentation was appropriate, with enzymes activities as follows: FPase = 410.76 U/gDM, CMCase = 351.96U/gDM, β-glucosidase = 16.37 U/gDM, xylanase = 6166.01 U/gDM and amyloglucosidase = 425.04 U/gDM (with maximum 993.71 U/gDM on day 6). In addition, the solid state fermentation significantly (P < 0.01) reduced the concentrations of NDF, ADF, cellulose and hemicellulose in the rice straw by 19.96, 13.8, 16.32 and 32.87%, respectively. The high degradation of the hemicellulose was reflected by the high activity of xylanase enzyme, which hydrolyses xylan in hemicellulose to xylose. Higher reducing sugar and microbial cell mass productions were also obtained after 8 days fermentation. Present data showed that, A. terreusis capable of producing high quantity of cellulolytic enzymes for the reduction of lignocellulose contents of biomass in a shorter incubation time when compared with the previously reported for biological treatment of agricultural by-products using white rot fungi.